Allotriophagy and Allotriodipsia in Endocrinology - Sanjay Kalra; Avivar Awasthi; Saurabh Arora; Nitin Kapoor (Journal of the Pakistan Medical Association, 2023)
Allotriophagy is defined as food cravings that are different from the expected or the norm. It gives clinical pointers to an underlying diagnosis. We propose a new term, allotriodipsia which suggests a preference for beverages that are different from the norm. Taken together, these two entities may point towards certain endocrinological abnormalities and iatrogenic sequelae. In this communication we highlight the clinical relevance of allotriophagy and allotriodipsia. Keywords: Allotriophagy, Allotriodipsia, Anorexia nervosa, Bulimia nervosa, Food fads, Orthorexia nervosa, Osteomalacia, Sheehan’s syndrome.